Ambiente laboral en el Registro de la Propiedad de Puebloviejo - Torres Reyes, Irvin Jerry (2018)
Since the beginning of the formation of companies, men have always represented the most valuable resource for this, since their participation is unpredictable. Especially human resources are the only living resource to create an adequate work environment within the organization and is the one that decides the management of others. In addition, it has a vocation aimed at growth and development.